Morphine Promotes Tumor Angiogenesis and Increases Breast Cancer Progression. (3rd May 2015) - Bimonte, Sabrina; Barbieri, Antonio; Rea, Domenica; Palma, Giuseppe; Luciano, Antonio; Cuomo, Arturo; Arra, Claudio; Izzo, Francesco
Abstract : Morphine is considered a highly potent analgesic agent used to relieve suffering of patients with cancer. Several in vitro and in vivo studies showed that morphine also modulates angiogenesis and regulates tumour cell growth. Unfortunately, the results obtained by these studies are still contradictory. In order to better dissect the role of morphine in cancer cell growth and angiogenesis we performed in vitro studies on ER-negative human breast carcinoma cells, MDA.MB231 and in vivo studies on heterotopic mouse model of human triple negative breast cancer, TNBC. We demonstrated that morphine in vitro enhanced the proliferation and inhibited the apoptosis of MDA.MB231 cells. In vivo studies performed on xenograft mouse model of TNBC revealed that tumours of mice treated with morphine were larger than those observed in other groups. Moreover, morphine was able to enhance the neoangiogenesis. Our data showed that morphine at clinical relevant doses promotes angiogenesis and increases breast cancer progression.